Description of Loffienema dhanoriensis gen. n., sp. n. (Nematoda: Rhabditidae) from Jammu and Kashmir State, India - Shah, Ali. A.; Allie, Kaisar Ahmad; Vaid, Shavish; Handoo, Zafar A. (Zootaxa, 2018)
A new genus, Loffienema dhanoriensis gen. n., sp. n. is described and illustrated from soil mixed with mature compost of Biodiversity Park, Baba Ghulam Shah Badshah (BGSB) University, Rajouri, Jammu and Kashmir, India. It is characterized by medium-sized body, slightly offset labial region, weakly developed, isoglottoid stegostom, amphidelphic reproductive system, slender and separate spicules, spathulate gubernaculum and reduced bursa with eight pairs of bursal rays. Its relationship and distinguishing features with other closely related genera are discussed.